Nailfold capillaroscopy in leprosy - Adma Silva de Lima; Vanessa Irusta dal Pizzol; Scheila Fritsch; Gabriela Poglia Fonseca; Fabiane Andrade Mulinari-Brenner; Carolina de Souza Muller; Vanessa Cristhine Dalombo Ottoboni (Sociedade Brasileira de Dermatologia, 2016)
Abstract: Due to mounting evidences of interaction between Hansen's bacilli with endothelial cells and the paucity of studies addressing the presence of nailfold capillaroscopic alterations in patients with Hansen's disease, a study was carried out in order to verify the presence of capillaroscopic alterations in patients with leprosy in its various forms and its correlation with clinical parameters. Ten patients were evaluated at a specialized university service. Sixty percent of those had some capillaroscopic change, such as micro-hemorrhages, ectatic, bushy and corkscrew capillaries. Such changes were unspecific, which suggests there is not a specific pattern for this disease.